2018
DOI: 10.3390/coatings8110392
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Potentiostatic Deposition of Micro-Particles on Al Alloy as Superhydrophobic Surface for Enhanced Corrosion Resistance by Reducing Interfacial Interactions

Abstract: Corrosion failure is a thorny problem that restricts the application of Al alloys. As a new technique for functional realization, hydrophobic preparation offers an efficient approach to solve corrosion problem. This work has developed a facile and low-cost method to endow Al alloy with enhanced water-repellent and anticorrosion abilities. The micro-particles have been firstly prepared by one-step deposition process. Furthermore, wetting and electrochemical behaviors of as-prepared structures have been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In Figure 2 a, the curve has an obvious impedance arc at 155 °C for 6 h. When the aging time is 12 h or 24 h, two impedance arcs appear at the frequency of 0.01–1 Hz or 1–1000 Hz, respectively. The arc at the low frequency is mainly caused by the electrochemical corrosion process, while the arc at the high frequency is related to the charge transfer resistance at the interfaces between the electrolyte solution and alloy [ 40 , 41 ]. Generally, a large impedance arc indicates a high impedance magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2 a, the curve has an obvious impedance arc at 155 °C for 6 h. When the aging time is 12 h or 24 h, two impedance arcs appear at the frequency of 0.01–1 Hz or 1–1000 Hz, respectively. The arc at the low frequency is mainly caused by the electrochemical corrosion process, while the arc at the high frequency is related to the charge transfer resistance at the interfaces between the electrolyte solution and alloy [ 40 , 41 ]. Generally, a large impedance arc indicates a high impedance magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…According to Equation ( 1), the value of the f s was calculated to be 10%, which demonstrated that when the sample was in contact with water, the air/liquid interface had occupied 90% of the apparent area. Moreover, the CH group in the attached FAS showed good resistance to OH bonding, which thus enhanced such liquid repellence [24]. Therefore, superhydrophobicity was attributed to the high proportion of trapped air on the sample surface and to the low surface energy derived from fluorine-containing groups.…”
Section: Coating Hydrophobicity Analysesmentioning
confidence: 99%
“…To the best of our knowledge, only few reference data are available [7,[14][15][16] about superhydrophobic surfaces in real seawater environments in a time window greater than days. Furthermore, in these works, no recyclable materials have been used.…”
Section: Introductionmentioning
confidence: 99%